Modeling success in life-span psychology: The principles of selection, optimization, and compensation - Lang, Frieder; Rohr, Margund; Williger, Bettina (Handbook of Life-Span Development, 2011)
This chapter provides an overview on the lifespan model Selection, Optimization, and Compensation with respect to theory and empirical findings. The chapter begins with a discussion of the meaning structure of success from a lifespan perspective and the general nature of development. The discussion of the three SOC principles also addresses critical issues related to the functionality of SOC principles, the coordination and sequencing of SOC, and the context-dependency of the mechanisms of SOC. The chapter also reviews three prototypical theoretical specifications of the SOC model with related empirical illustrations: The resource-allocation SOC model, the action-theoretical SOC model, and the context-theoretical SOC model. It is argued that SOC is often reflected in accumulated environmental structures of the developmental context. Such contexts reflect accumulated impacts of SOC principles in human cultures over time. The chapter ends with a discussion of the future potential of the SOC model giving an outlook on open research issues.
Keywords: Successful Aging; Selection; Optimization; Compensation